INTERVENSI LEAN-MED BERBASIS DATA EPIDEMIOLOGIS LOKAL DALAM MENURUNKAN WAKTU TUNGGU PASIEN RAWAT JALAN DI RUMAH SAKIT RUJUKAN SAMARINDA - Ardan, M.; Rahman, Ferry Fadzlul (Poltekkes Kemenkes Bandung, 2025)
Outpatient waiting time remains a persistent challenge in hospital management, especially amid rising service demands and patient expectations. This study applied a Lean Management for Healthcare Delivery (Lean-Med) intervention based on epidemiological findings, including peak visit times, patient distribution per clinic, and staff workload imbalances. A quasi-experimental pre–post design was used involving 120 respondents (60 pre- and 60 post-intervention) selected via purposive sampling across three priority clinics: internal medicine, neurology, and pulmonology. The intervention included digital queue systems, physician schedule adjustments, and pharmacy service optimization.Paired t-test analysis showed a significant reduction in total waiting time from 129 to 69 minutes (46% decrease, p < 0.001). All service components, from registration to medication retrieval, saw statistically significant reductions. Patient satisfaction improved from 3.3 to 4.2 (p < 0.001), especially regarding information clarity, waiting time, and service accuracy. Healthcare staff workload was more evenly distributed (p = 0.012), notably in pulmonology after the addition of personnel, reducing clinical load from 37.8 to 28.3 patients per provider. These findings affirm that Lean-Med, when aligned with epidemiological insights, offers a transformational strategy for improving hospital service delivery and responsiveness under high patient volume conditions.